Towards a thermo-mechanical characterization approach of buildings' envelope - Soukayna Berrabah; Mohamed Ould Moussa; Mohamed Bakhouya (Energy Reports, 2020)
This paper investigates the numerical and experimental thermo-mechanical characterization of buildings' structure for energy efficiency. A finite element model (FEM) of a small-scaled building is carried out using mesh refining tools at thermal bridges zones. The latter is revealed towards infra-red (IR) camera measurements. Galvanized steel is the main material composing the building's walls in which heat transfer coefficients are determined based on measurements of external and internal averaged temperatures. Hence, the physical model includes thermal conductivity, heat convective and radiative phenomena. Results of computations, made with finite elements method, using the cast3m tool, show a good agreement compared to those obtained from experiments.
Keywords: 330; Energy efficiency in buildings; FEM; Infrared camera; Materials; Thermo-mechanical characterization